2020
DOI: 10.1111/ppl.13064
|View full text |Cite
|
Sign up to set email alerts
|

Stress responsive gene regulation in relation to hydrogen sulfide in plants under abiotic stress

Abstract: Plants often face a variety of abiotic stresses, which affects them negatively and lead to yield loss. The antioxidant system efficiently removes excessive reactive oxygen species and maintains redox homeostasis in plants. With better understanding of these protective mechanisms, recently the concept of hydrogen sulfide (H2S) and its role in cell signaling has become the center of attention. H2S has been recognized as a third gasotransmitter and a potent regulator of growth and development processes such as ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(48 citation statements)
references
References 130 publications
(214 reference statements)
1
45
0
2
Order By: Relevance
“…As a small gaseous signaling molecule, H 2 S readily traverses the intracellular and intercellular domains, and plays a key role in regulating the homeostasis in plant cells (Papanatsiou et al 2015 ). H 2 S has been identified as a brilliant defender against different stresses such as drought, heat, chilling, heavy metals, osmotic and saline (Pandey and Gautam 2020 ) (Fig. 2 ).…”
Section: H 2 S Positively Responds To Biotic and Amentioning
confidence: 99%
See 1 more Smart Citation
“…As a small gaseous signaling molecule, H 2 S readily traverses the intracellular and intercellular domains, and plays a key role in regulating the homeostasis in plant cells (Papanatsiou et al 2015 ). H 2 S has been identified as a brilliant defender against different stresses such as drought, heat, chilling, heavy metals, osmotic and saline (Pandey and Gautam 2020 ) (Fig. 2 ).…”
Section: H 2 S Positively Responds To Biotic and Amentioning
confidence: 99%
“…H 2 S can help the plants to resist a variety of abiotic stresses such as drought, cold, heat, salinity, hypoxia and toxic metal to effectively alleviate their damages (Pandey and Gautam 2020 ; Zhang et al 2021 ), which is closely associated with the classic “rescue” mode of H 2 S. Continuous exposure to any abiotic stress will cause an imbalance of endogenous redox homeostasis. Excessive accumulations of reactive oxygen species (ROS), hydrogen peroxide (H 2 O 2 ) and superoxide anion (O 2 −• ), will further lead to lipid peroxidation, protein oxidation and damage to plant cells, resulting in autophagy and programmed cell death (PCD) (Da-Silva and Modolo 2018 ; Hancock 2017 ).…”
Section: H 2 S Positively Responds To Biotic and Amentioning
confidence: 99%
“…Rai et al (2019) have given an overview of NO and salicylic acid signaling towards acquired heat tolerance in plants. Paul and Roychoudhury (2019), Pandey and Gautam (2019) Research articles have covered diverse new roles of H 2 S and NO in regulating abiotic stress in plants. Kushwaha and Singh (2019) and Ahmad et al (2019) have reported various mechanisms through which H 2 S regulates chromium toxicity in crop plants.…”
mentioning
confidence: 99%
“…Rai et al () have given an overview of NO and salicylic acid signaling towards acquired heat tolerance in plants. Paul and Roychoudhury (), Pandey and Gautam () and Singh et al (2019) have covered exhaustive current roles of H 2 S and NO in plants under changing environmental conditions. Finally, Sharma et al () and Shivaraj et al () have discussed molecular mechanisms and crosstalk of NO and H 2 S in metal stress tolerance.…”
mentioning
confidence: 99%
“…Upon its production, H 2 S can be highly mobile across plant membranes and can either be influxed in or effluxed out of the plant system as a way out against heavy metal stress ( Shivaraj et al, 2020 ). Plant stress adaptation against heavy metal in H 2 S-treated plant is initiated via antioxidant activities ( Kushwaha and Singh, 2019 ), accumulation of osmoregulators ( Tian et al, 2016 ), cell signaling protein ( He et al, 2019 ), and by different gene expressions ( Pandey and Gautam, 2019 ). Overall, it enables plants to combat against stress factor such as heavy metals via effective removal of reactive oxygen species (ROS) by adjusting intracellular redox balance.…”
Section: Introductionmentioning
confidence: 99%